Pengaruh Gaya Kepemipinan dan Kesejahteraan Karyawan terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening pada PT. Kilang Lima Gunung Lubuk Begalung Padang - Josep Parulian Pakpahan; Vicky Brama Kumbara; Chintya Ones Charli (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
Many factors influence employee performance, including leadership style, employee welfare, and job satisfaction. At PT Kilang Lima Gunung Lubuk Begalung Padang, there is a decrease in employee performance among most employees, as seen from the company's production level that does not meet the company's target. This study aims to analyze the influence of leadership style and employee welfare on employee performance with job satisfaction as an intervening variable at PT Kilang Lima Gunung Lubuk Begalung Padang. This study uses a quantitative research method that explores the influence between independent variables and dependent variables. The research data is collected through a survey questionnaire from 105 respondents and tested using Smart PLS (Partial Least Square). The results show that leadership style and employee welfare have a significant impact on job satisfaction and employee performance. As a recommendation, this study suggests that the company should focus on improving employee welfare and leadership style to enhance job satisfaction and employee performance.